Influence of Grain‐Scale Properties on Localization Patterns and Slip Weakening Within Dense Granular Fault Gouges. Issue 3 (21st March 2023) - Casas, N.; Mollon, G.; Daouadji, A.
Abstract: Fault zones are usually composed of a granular gouge, coming from the wear material of previous slips, which contributes to friction stability. When considering a mature enough fault zone that has already been sheared, different types of infill materials can be observed, from mineral cementation to matrix particles that can fill the remaining pore spaces between clasts and change the rheological and frictional behaviors of the gouge. We aim to understand and reproduce the influence of grain‐scale characteristics on slip mechanisms and gouge rheology (Riedel bands) by employing the discrete element method. A 2D‐direct shear model is considered with a dense assembly of small polygonal cells of matrix particles. A variation of gouge characteristics such as interparticle friction, gouge shear modulus or the number of particles within the gouge thickness leads to different Riedel shear band formation and orientation that has been identified as an indicator of a change in slip stability. Interpreting results with slip weakening theory, our simulated gouge materials with high interparticle friction or a high bulk shear modulus, increase the possible occurrence of dynamic slip instabilities (small nucleation length and high breakdown energy). They may give rise to faster earthquake ruptures. Plain Language Summary: The center of a seismic fault zone is usually composed of a material with granular particles highly contributing to the way the fault moves. This zone may be composed of various infill materials from mineral cementation to smaller particles that can fill the remaining pore spaces between larger particles and change the properties of the fault zone. We aim to understand and reproduce the influence of grain‐scale characteristics on slip mechanisms by employing numerical simulations. A variation of granular particle characteristics leads to different deformation patterns that can be identified as an indicator of a change in slip stability. The obtained results suggest that some granular materials with high interparticle friction or a high bulk shear modulus, increase the possible occurrence of dynamic slip instabilities which may lead to faster earthquake ruptures. This work investigates in more depth the link between the characteristics of the granular material, the deformations of the fault core, and the possible occurrence of an earthquake. Key Points: 2D‐discrete element method simulations performed on numerical fault gouges composed of a very dense assembly of polygonal‐shaped particles A small change in grain‐scale gouge properties impacts Riedel shear band formation, their orientation angle and the type of Riedel structure formed High interparticle friction and high bulk shear modulus increase the breakdown energy and the occurrence of dynamic slip instabilities